PERAN BUDAYA RELIGIUS DALAM PEMBENTUKAN KARAKTER LEMBAGA PENDIDIKAN ISLAM - khusnul hamdani, mohammad (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to examine the role of religious culture in character building in Islamic educational institutions, especially in the digital era that faces moral challenges. The cultivation of religious values, such as honesty and responsibility, is considered important to build students' character with integrity. The method used is qualitative with a literature study approach, which involves analyzing related literature. The results showed that the implementation of a religious culture can improve students' discipline, empathy and social care. However, challenges such as limited resources and resistance to change need to be overcome to optimize the implementation of religious culture. A successful example can be seen at MI Tahfidz Al-Furqon Ponorogo, which successfully integrates Islamic values in daily activities, involving collaboration between the school and parents. A religious culture not only shapes individuals with good morals, but also contributes to the creation of a harmonious and civilized society. This research emphasizes the importance of integrating religious values in the education curriculum to build a young generation that is competitive and able to face the negative influence of globalization.